Quantification of the effects of melittin on liposome structure. (26th October 2005) - Popplewell, J.; Freeman, N.; Carrington, S.; Ronan, G.; McDonnell, C.; Ford, R.C.
Abstract : An optical technique, dual-polarization interferometry, has been used to examine lipid structures at the solid/liquid interface. Changes in the lipid structures, in real time, were examined as a consequence of challenging them with a peptide (melittin) that is known to induce liposome rupture. This work suggests that it should be possible to obtain a better understanding of the detail of the melittin rupture process.